1991
DOI: 10.3177/jnsv.37.401
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Serum Phospholipids in an Elderly Institutionalized Japanese Population.

Abstract: SummaryThe fatty acid composition of serum phospholipids of 277 persons, aged 63-97y (average 78y), was measured. Subjects had been living independently in a facility with full food service for 1y or more. Eleven saturated and unsaturated fatty acids were detected in all the subjects. Stearic acid (18:0) was positively (p=0.028) and dihomo gamma-linolenic acid (20:3 n-6) was negatively (p=0.012) related to age. Arachidonic acid (20:4 n-6) tended to decline with age (p=0.063). In addition, the oleic acid (18:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This exclusion criterion was set because it has been shown that elderly men with higher ARA levels might be difficult to show a response to ARA supplementation on the P300 evaluation 26 . However, ARA content of participants in the present study was 8.7 and was in the normal range of Japanese elderly 6.4 41 44 in serum/plasma phospholipids . These data suggest that the participants in the present study were not selected from a limited and special population but represent a general population of Japanese elderly men.…”
Section: Discussionmentioning
confidence: 83%
“…This exclusion criterion was set because it has been shown that elderly men with higher ARA levels might be difficult to show a response to ARA supplementation on the P300 evaluation 26 . However, ARA content of participants in the present study was 8.7 and was in the normal range of Japanese elderly 6.4 41 44 in serum/plasma phospholipids . These data suggest that the participants in the present study were not selected from a limited and special population but represent a general population of Japanese elderly men.…”
Section: Discussionmentioning
confidence: 83%
“…It is, however, lower than ®gures observed in Japan (Yamori et al, 1985;Takahashi et al, 1991). Likewise, the Norwegian consumption of ®sh and ®sh products is considerably higher than in most Western populations (Houwelingen van et al, 1989;Holst, 1991), but not as high as in Japan (Tominaga & Kato 1992;Iso et al, 1989).…”
Section: Serum Phospholipid Fatty Acid Compositionmentioning
confidence: 90%
“…Sex and age, which are the characteristics most often taken into consideration (Holman et al, 1979;Takahashi et al, 1991) were the same for all participants in our study. Other factors may in¯uence the serum phospholipid fatty acid composition.…”
Section: Serum Phospholipid Fatty Acid Compositionmentioning
confidence: 99%
“…In addition to inaccurate answers in the questionnaire, the difference in bioavailability of fatty acids in children and adults may attenuate the correlations. Among adults over the age of 30 y, older people have more serum EPA, DPA, and DHA (10,47,48); fatty acid content of RBCs may be lower in children than in adults. Furthermore, because RBC fatty acids could indicate a steady-state equilibrium or a transient state with new fatty acids to be delivered to a body compartment (49), RBC n-3 PUFAs, precursors of physiologically active substances, may not reflect dietary intake in children during maturation and weight gain (18).…”
Section: Discussionmentioning
confidence: 99%